Behaviour of reinforced concrete beams with opening added with kenaf fiber - Nazmin, Zulaili (2018)
This paper presents the findings of an experimental research program that was conducted to improve the structural behaviour of natural fiber reinforced concrete (FRC) beam with opening at end which is made using kenaf fiber. Appropriate mixture proportions and mixing procedures are calculated to produce beam with kenaf volume fractions, Vf of 0%, 1% and 2%. The compressive strength, flexural strength of kenaf fiber reinforced concrete (KFRC) specimens are presented and compared to the behaviour of plain concrete control specimens. The experimental results indicate that the behaviour of KFRC and compression test were both decreasing with increasing volume of fraction.